2020
DOI: 10.1155/2020/8072639
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin Exerts Antitumor Activity via Downregulation of Skp2 in Breast Cancer Cells

Abstract: Background. Breast cancer is the common malignancy with high morbidity and mortality in women. S-phase kinase-associated protein 2 (Skp2) has been characterized to play an oncogenic role in the breast carcinogenesis and progression. Therefore, inactivation of Skp2 in breast cancer might be a novel approach for fighting breast malignancy. A natural compound diosgenin has been reported to exert anticancer activity in a variety of human cancers. However, the underlying mechanism has not been fully determined. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…Interestingly, diosgenin at concentrations greater than 5 μM reduced IL-8 and IL-2 production in a concentration-dependent manner ( Figure 6 A,C). As a previous study has reported the cytotoxic effect of diosgenin, the impact of diosgenin on the viability of Caco-2 cells and OVA-primed MLN cells was further explored [ 26 ]. Concordantly, diosgenin at concentrations greater than 20 μM diminished cell viability in a concentration-dependent manner ( Figure 6 B,D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, diosgenin at concentrations greater than 5 μM reduced IL-8 and IL-2 production in a concentration-dependent manner ( Figure 6 A,C). As a previous study has reported the cytotoxic effect of diosgenin, the impact of diosgenin on the viability of Caco-2 cells and OVA-primed MLN cells was further explored [ 26 ]. Concordantly, diosgenin at concentrations greater than 20 μM diminished cell viability in a concentration-dependent manner ( Figure 6 B,D).…”
Section: Resultsmentioning
confidence: 99%
“…A previously described in vitro method for investigating the impact of diosgenin on cells was employed [ 26 ]. Briefly, Caco-2 cells or OVA-primed MLN cells were incubated with various concentrations of diosgenin (0–200 μM) for 14 and 24 h, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, diosgenin had the highest DL property and OB value. The main component of Dioscorea opposita regulates the Cdc25C-Cdc2-cyclin B pathway in and the mitochondrial-mediated apoptosis of human breast cancer cell lines to induce G2/M phase arrest, and it may be a potential inhibitor of Skp2, with the ability to reduce cell viability and induce apoptosis 14,15 . In addition, diosgenin signi cantly inhibits actin polymerization, Vav2 phosphorylation and Cdc42 activation to inhibit the migration of MDA-MB-231 cells, the conferring antimetastatic potential 16 .…”
Section: Discussionmentioning
confidence: 99%
“…High expression of Skp2 has been observed in various human cancers and is associated with poor prognosis and adverse therapeutic outcomes, suggesting that Skp2 functions as an oncogene [ 7 , 8 ]. Inhibition of Skp2 expression has been shown to exhibit a potent anti-proliferative effect in various cancer models [ 9 - 11 ].…”
Section: Introductionmentioning
confidence: 99%